Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Recent insights in the development and functions of insect hemocytes - Michael R Strand (Current Opinion in Insect Science, 2026)

Insulin-like peptides and ovary ecdysteroidogenic hormone differentially stimulate physiological processes regulating egg formation in the mosquito Aedes aegypti - Kangkang Chen; Xiaoyi Dou; Jai Hoon Eum; Ruby E. Harrison; Mark R. Brown; Michael R. Strand (Insect Biochemistry and Molecular Biology, 2023)

An aphid symbiont confers protection against a specialized RNA virus, another increases vulnerability to the same pathogen - Clesson H. V. Higashi; William L. Nichols; Germain Chevignon; Vilas Patel; Suzanne E. Allison; Kyungsun Lee Kim; Michael R. Strand; Kerry M. Oliver (Molecular Ecology, 2023)
Insects often harbour heritable symbionts that provide defence against specialized natural enemies, yet little is known about symbiont protection when hosts face simultaneous threats. In pea aphids ( Acyrthosiphon pisum ), the facultative endosymbiont Hamiltonella defensa confers protection against the parasitoid, Aphidius ervi , and Regiella insecticola protects against aphid‐specific fungal pathogens, including Pandora neoaphidis . Here, we investigated whether these two common aphid symbionts protect against a specialized virus A . pisum virus (APV), and whether their antifungal and antiparasitoid services are impacted by APV infection. We found that APV imposed large fitness costs on symbiont‐free aphids and these costs were elevated in aphids also housing H . defensa . In contrast, APV titres were significantly reduced and costs to APV infection were largely eliminated in aphids with R . insecticola . To our knowledge, R . insecticola is the first aphid symbiont shown to protect against a viral pathogen, and only the second arthropod symbiont reported to do so. In contrast, APV infection did not impact the protective services of either R . insecticola or H . defensa . To better understand APV biology, we produced five genomes and examined transmission routes. We found that moderate rates of vertical transmission, combined with horizontal transfer through food plants, were the major route of APV spread, although lateral transfer by parasitoids also occurred. Transmission was unaffected by facultative symbionts. In summary, the presence and species identity of facultative symbionts resulted in highly divergent outcomes for aphids infected with APV, while not impacting defensive services that target other enemies. These findings add to the diverse phenotypes conferred by aphid symbionts, and to the growing body of work highlighting extensive variation in symbiont‐mediated interactions.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Explaining the worldwide distributions of two highly mobile species: Cakile edentula and Cakile maritima - Elliot C. Shaw; Rachael Fowler; Sara Ohadi; Michael J. Bayly; Rosemary A. Barrett; Josquin Tibbits; Allan Strand; Charles G. Willis; Kathleen Donohue; Philipp Robeck; Roger D. Cousens (Journal of Biogeography, 2021)
Aim If we are able to determine the geographic origin of an invasion, as well as its known area of introduction, we can better appreciate the innate environmental tolerance of a species and the strength of selection for adaptation that colonizing populations have undergone. It also enables us to maximize the success of searches for effective biological control agents. We determined the number of successful colonization events that have occurred throughout the world for two Cakile species and compared the climates from which they originated, in which they established and then spread. Location Worldwide. Taxon Sea‐Rockets ( Cakile spp.), Brassicaceae. Methods We used a high‐throughput sequencing and a genome skimming approach combined with Bayesian Inference phylogenetics to examine variation in entire chloroplast genomes and regions of nuclear ribosomal DNA within native and introduced areas. Databases were used to compare climates between native ranges and introduced regions for multiple clades within each species. Results At least seven clades have invaded different regions of the world. In most cases we were able to identify their source regions and climates. The environmental bottlenecks differed in intensity: while some clades colonized into climates that were similar to climates in their native range, other clades had a very broad innate environmental tolerance such that new invasions succeeded beyond the climate range of native populations. We found clear evidence of hybridization—specifically, chloroplast capture—between two species in Australia. Conclusions Results here show that these species are sometimes capable of colonizing in climates that are beyond the climate range of native populations. Whether successful colonization beyond native climate niches requires de novo adaptation, or whether it represents an innate broad fundamental niche requires further investigation. Cakile species provide an excellent opportunity to study replicated climate adaptation trajectories.

Trichoplusia ni and Chrysodeixis includens larvae show different susceptibility to Chrysodeixis includens single nucleopolyhedrovirus per os infection - Fabricio da Silva Morgado; Leonardo Assis Silva; Laryssa Moreira Bernardes; Cecilia Czepak; Michael R. Strand; Bergmann Morais Ribeiro (Journal of Pest Science, 2020)

Forecasting the genetic influences of red drum stock enhancement in South Carolina - Christopher J. Katalinas; John D. Robinson; Allan E. Strand; Tanya Darden; Karl Brenkert; Michael R. Denson (Fisheries Management and Ecology, 2019)
The South Carolina Department of Natural Resources ( SCDNR ) began stocking red drum, Sciaenops ocellatus (Linnaeus), in 1989 to augment the abundance of juveniles available for recreational harvest in South Carolina estuaries. While stock enhancement can help supplement wild populations under high fishing pressure, releasing hatchery‐raised fish into the wild also presents the risk of decreased genetic diversity. An individual‐based model ( IBM ) was developed to forecast the genetic influences of stocking on the wild spawning population to inform responsible stocking strategies. Model results indicated the SCDNR red drum stock enhancement programme should maintain mean contributions of stocked fish no greater than 30% per year class over a 45‐year stocking period, coupled with at least 10 effective breeders in the hatchery replaced annually, to maintain current levels of genetic diversity estimated in the wild population. The IBM is a useful tool for hatchery managers to guide responsible stock enhancement.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Mosquitoes host communities of bacteria that are essential for development but vary greatly between local habitats - Kerri L. Coon; Mark R. Brown; Michael R. Strand (Molecular Ecology, 2016)
Mosquitoes are insects of interest because several species vector disease‐causing pathogens to humans and other vertebrates. We previously reported that mosquitoes from long‐term laboratory cultures require living bacteria in their gut to develop, but development does not depend on particular species of bacteria. Here, we focused on three distinct but interrelated areas of study to better understand the role of bacteria in mosquito development by studying field and laboratory populations of Aedes aegypti , Aedes albopictus and Culex quinquefasciatus from the southeastern United States. Sequence analysis of bacterial 16S rRNA gene amplicons showed that bacterial community composition differed substantially in larvae from different collection sites, whereas larvae from the same site shared similarities. Although previously unknown to be infected by Wolbachia , results also indicated that Ae. aegypti from one field site hosted a dual infection. Regardless of collection site or factors like Wolbachia infection, however, each mosquito species required living bacteria in their digestive tract to develop. Results also identified several concerns in using antibiotics to eliminate the bacterial community in larvae in order to study its developmental consequences. Altogether, our results indicate that several mosquito species require living bacteria for development. We also hypothesize these species do not rely on particular bacteria because larvae do not reliably encounter the same bacteria in the aquatic habitats they develop in.

Development and testing of a prototype tool for integrated assessment of chemical status in marine environments - Jesper H. Andersen; Ciarán Murray; Martin M. Larsen; Norman Green; Tore Høgåsen; Elin Dahlgren; Galina Garnaga-Budrė; Kim Gustavson; Michael Haarich; Emilie M.F. Kallenbach; Jaakko Mannio; Jakob Strand; et al. (Environmental Monitoring and Assessment, 2016)

Mosquitoes rely on their gut microbiota for development - Kerri L. Coon; Kevin J. Vogel; Mark R. Brown; Michael R. Strand (Molecular Ecology, 2014)
Field studies indicate adult mosquitoes ( C ulicidae) host low diversity communities of bacteria that vary greatly among individuals and species. In contrast, it remains unclear how adult mosquitoes acquire their microbiome, what influences community structure, and whether the microbiome is important for survival. Here, we used pyrosequencing of 16S r RNA to characterize the bacterial communities of three mosquito species reared under identical conditions. Two of these species, A edes aegypti and A nopheles gambiae , are anautogenous and must blood‐feed to produce eggs, while one, G eorgecraigius atropalpus , is autogenous and produces eggs without blood feeding. Each mosquito species contained a low diversity community comprised primarily of aerobic bacteria acquired from the aquatic habitat in which larvae developed. Our results suggested that the communities in A e. aegypti and A n. gambiae larvae share more similarities with one another than with G . atropalpus . Studies with A e. aegypti also strongly suggested that adults transstadially acquired several members of the larval bacterial community, but only four genera of bacteria present in blood fed females were detected on eggs. Functional assays showed that axenic larvae of each species failed to develop beyond the first instar. Experiments with A e. aegypti indicated several members of the microbial community and E scherichia coli successfully colonized axenic larvae and rescued development. Overall, our results provide new insights about the acquisition and structure of bacterial communities in mosquitoes. They also indicate that three mosquito species spanning the breadth of the C ulicidae depend on their gut microbiome for development.

Systematic analysis of a wasp parasitism arsenal - Gaelen R. Burke; Michael R. Strand (Molecular Ecology, 2014)
Parasitoid wasps are among the most diverse insects on earth with many species causing major mortality in host populations. Parasitoids introduce a variety of factors into hosts to promote parasitism, including symbiotic viruses, venom, teratocytes and wasp larvae. Polydnavirus‐carrying wasps use viruses to globally suppress host immunity and prevent rejection of developing parasites. Although prior results provide detailed insights into the genes viruses deliver to hosts, little is known about other products. RNA seq and proteomics were used to characterize the proteins secreted by venom glands, teratocytes and larvae from M icroplitis demolitor, which carries M . demolitor bracovirus (Md BV ). These data revealed that venom glands and teratocytes secrete large amounts of a small number of products relative to ovaries and larvae. Venom and teratocyte products exhibited almost no overlap with one another or Md BV genes, which suggested that M . demolitor effector molecules are functionally partitioned according to their source. This finding was well illustrated in the case of Md BV and teratocytes. Many viral proteins have immunosuppressive functions that include disruption of antimicrobial peptide production, yet this study showed that teratocytes express high levels of the antimicrobial peptide hymenoptaecin, which likely compensates for Md BV ‐mediated immunosuppression. A second key finding was the prevalence of duplications among genes encoding venom and teratocyte molecules. Several of these gene families share similarities with proteins from other species, while also showing specificity of expression in venom glands or teratocytes. Overall, these results provide the first comprehensive analysis of the proteins a polydnavirus‐carrying wasp introduces into its host.

Oxidative stress protection and the repair response to hydrogen peroxide in the hyperthermophilic archaeon Pyrococcus furiosus and in related species - Kari R. Strand; Chengjun Sun; Ting Li; Francis E. Jenney; Gerrit J. Schut; Michael W. W. Adams (Archives of Microbiology, 2010)

High‐resolution determination of coral reef bottom cover from multispectral fluorescence laser line scan imagery - Charles H. Mazel; Michael P. Strand; Michael P. Lesser; Michael P. Crosby; Bryan Coles; Andrew J. Nevis (Limnology and Oceanography, 2003)
A prototype in‐water laser line‐scanning multispectral fluorescence imaging system was evaluated for its ability to provide data that could be used to determine the quantitative distribution and abundance of various functional groups on coral reefs. The system collected fluorescence imagery in three spectral bands with 1 cm 2 resolution at sites in Florida and the Bahamas. Fluorescence excitation was at 488 nm, and imagery was collected in emission bands centered at 520, 580, and 685 nm. Ground truth data on bottom cover was collected by divers using conventional line transect and photographic quadrat methods. A set of classification rules based on the relative signal levels in the three fluorescence channels was developed to assign the image pixels to functional groups. Once the image was classified, percent cover data for the groups were computed for the full image and for subsets of the image chosen to simulate line transect, grid survey, and photographic quadrat surveys. The statistics of percent cover of various bottom types derived from the fluorescence image compared favorably with those determined by diver survey techniques. The results demonstrate that fluorescence imaging has the long‐term potential to provide coverage of large spatial areas of coral reefs at high resolution, with automated classification and quantification of functional groups in the image.

Underwater Optical Imaging: Status and Prospects - Julles Jaffe; Karl Moore; John McLean; Michael Strand (Oceanography, 2001)

Evaluation of several degree-day estimation methods in California climates - William J. Roltsch; Frank G. Zalom; Ann J. Strawn; Joyce F. Strand; Michael J. Pitcairn (International Journal of Biometeorology, 1999)

Constrained oviposition and female-biased sex allocation in a parasitic wasp - P. J. Ode; Michael F. Antolin; Michael R. Strand (Oecologia, 1997)